Detection of Emodin Derived Glutathione Adduct in Normal Rats Administered with Large Dosage of Polygoni Multiflori Radix - Li-Long Jiang; Dong-Sheng Zhao; Ya-Xi Fan; Qiong Yu; Ping Li; Hui-Jun Li (Frontiers Media S.A., 2017)
Polygoni Multiflori Radix (PMR) has been commonly used as a tonic in China for centuries. PMR-associated hepatotoxicity has been drawing increasingly more attention in recent years in parallel with its wide utilization. Anthraquinones (AQs) are recognized as the main hepatotoxic components in PMR. However, the exact underlying mechanism of AQs poisoning is still not fully understood. Herein, we proposed a hypothesis that metabolic activation of AQs such as emodin was involved in PMR-induced liver injury, AQs followed to generate the electrophilic reactive metabolites and subsequently formed covalent adduct with cellular nucleophiles in the liver to exert hepatotoxicity. In the present study, the link of cytotoxicity of PMR in primary human hepatocytes and the depletion of glutathione (GSH) was investigated by MTT assay and UHPLC-QqQ-MS/MS analysis. The results showed that PMR depleted GSH and therefore induced cytotoxicity. Then, emodin-GSH adduct was identified in bile of liver injured rats after intragastric administration of PMR or emodin with the aid of UHPLC-QTOF-MS/MS method. Our findings not only provided confirmative evidence that the mechanism of hepatotoxicity induced by AQs in PMR involved key metabolic steps, but also revealed that emodin-GSH adduct had potential to be further developed as a sensitive and traceable biomarker for the assessment of PMR-induced liver injury.